Sugar apple (annona squamosa l., annonaceae) seed germination: morphological and anatomical changes (2013)
The anon or sugar apple is a species of the Annona genus, widely distributed in the world and in Colombia and a fruit with great potential in domestic and international markets. However, the technical information related to the aspects of propagation and production is limited. In the present study, the morphological and anatomical changes during seed germination of the sugar apple were determined using histological techniques and photographic records. The results show that seed germination is a process that takes place in two stages: testa rupture and endosperm rupture-radicle protrusion. In the post-germination stages, the induction and formation of lateral roots that were endogenously produced from the primary root from the pericycle were seen. The endosperm underwent morphological changes that increased its volume during imbibition and degraded in the final stages of germination, which could be indicative of endosperm weakening and reduction of mechanical strength imposed by embryo growth, which was required to complete germination in A. squamosa.